Crosstalk bandwidth and stability analysis in graphene nanoribbon interconnects. Issue 8 (July 2015) - Bagheri, Amin; Ranjbar, Mahboubeh; Haji-Nasiri, Saeed; Mirzakuchaki, Sattar
Graphical abstract: Highlights: TL modeling and matrix formulation for coupled MLGNR interconnects are used. PM/GM in near-end output increased, by increasing length or decreasing width. Crosstalk effects on victim line increased by increasing either length or width. Bandwidth of near-end output increased, by increasing width or decreasing length. The proposed TL model of coupled MLGNR interconnects has an excellent accuracy. Abstract: Based on transmission line modeling (TLM), and using the Nichols chart, we present a bandwidth and stability analysis, together with step time responses, for coupled multilayer graphene nanoribbon (MLGNR) interconnects that is inquired for the first time. In this analysis, the dependence of the degree of crosstalk relative stability for coupled MLGNR interconnects comprising of both capacitive and mutual-inductive couplings between adjacent MLGNR has been acquired. The obtained results show that with increasing the length or decreasing the width of the MLGNRs, the stability in near-end output increases. While, any increase in the length or width of MLGNRs, decrease the stability of far-end output. Also, by increasing capacitive coupling or decreasing inductive coupling, the near-end output becomes more stable, and the far-end output becomes less stable. Moreover, any increase in the length or capacitive coupling, decreases the bandwidth, whereas any increase in the width or inductive coupling, increases the bandwidth. Finally, transient simulations with Advanced Design System (ADS) show that the model has an excellent accuracy.